Perbedaan Jumlah Mata Tunas per Stek dan Populasi pada Pertumbuhan dan Produksi Bibit setelah Panen Ubi Kayu - Sutrisno Sutrisno; Kartika Noerwijati; Yuliantoro Baliadi; Sri Wahyuningsih; Abdullah Taufiq (Jurnal Ilmu Pertanian Indonesia, 2023)
Limitations of cuttings become an essential problem in the expansion of cassava plantations. One strategy that can be taken is to reduce the length of the cuttings and increase the plant population to increase the area planted and produce more stems per unit area for the next growing season. This study aimed to determine the effect of cutting length and plant population per hectare on the growth and production of cassava stems. The research was carried out at the Jambegede Agricultural Technology Research and Assessment Installation in February–December 2020. The treatment consisted of two factors, namely three levels of cutting length (2, 4, and 10 buds/cutting) and three levels of the population (10,000, 30,000, and 40,000 plants/ha). The experiment used the Malang-4 variety and was applied to a completely randomized split-plot experimental design of three groups with the population as the main plot and the number of buds as sub-plots. The results showed that the number of buds/cutting increased the number of growing plants, one and three-month plant height, the number of viable stems, the length of unfit stems for seedlings, and decreased the percentage of dead plants. On the other hand, plant population/ha increases the percentage of dead plants, stem length unsuitable for seeds, and number of stems suitable for seeds. The interaction between the number of buds/cutting and the population was seen in the diameter of the three-month-old stems, the number of stems unsuitable for seedlings, the number of plants grown, the number of dead plants, and the number of plants harvested. Keywords: cassava, length of cuttings, number of buds, plant population, stem production